2020
DOI: 10.1093/humupd/dmz044
|View full text |Cite
|
Sign up to set email alerts
|

Hypothetical roadmap towards endometriosis: prenatal endocrine-disrupting chemical pollutant exposure, anogenital distance, gut-genital microbiota and subclinical infections

Abstract: BACKGROUND Endometriosis is a gynaecological hormone-dependent disorder that is defined by histological lesions generated by the growth of endometrial-like tissue out of the uterus cavity, most commonly engrafted within the peritoneal cavity, although these lesions can also be located in distant organs. Endometriosis affects ~10% of women of reproductive age, frequently producing severe and, sometimes, incapacitating symptoms, including chronic pelvic pain, dysmenorrhea and dyspareunia, among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 306 publications
3
49
0
Order By: Relevance
“…Phthalates are common synthetic chemicals with ubiquitous exposures in our daily life. Till now, several epidemiologic evidences have reported that phthalates might be toxic to the male and female reproductive system 37 . Studies from laboratory examinations showed that phthalates interacted with the female reproductive system in animal models; these findings support the potential hazardous effects of phthalates in women.…”
Section: Effects Of Phthalate On Granulosa Cellsmentioning
confidence: 80%
See 1 more Smart Citation
“…Phthalates are common synthetic chemicals with ubiquitous exposures in our daily life. Till now, several epidemiologic evidences have reported that phthalates might be toxic to the male and female reproductive system 37 . Studies from laboratory examinations showed that phthalates interacted with the female reproductive system in animal models; these findings support the potential hazardous effects of phthalates in women.…”
Section: Effects Of Phthalate On Granulosa Cellsmentioning
confidence: 80%
“…Previous studies have demonstrated that sexually mature female rats exposed to di (2‐ethylhexyl) phthalate (DEHP) and its metabolite, mono (2‐ethylhexyl) phthalate (MEHP) showed a decrease in serum progesterone, delayed ovulation, and smaller preovulatory follicles with high levels of serum follicle‐stimulating hormone (FSH) 17,19,34,35 . Many studies demonstrated that phthalate exposure is significantly associated with endometriosis 10,36‐40 …”
Section: Introductionmentioning
confidence: 99%
“…The most widely accepted hypothesis is represented by the retrograde menstruation theory, characterised by the backward flux of menstrual debris that contains viable endometrial cells through the fallopian tubes into the pelvic cavity (20). However, some authors suggest an intrauterine origin of the disease (21,22), and the potential role of early-life influences, such as intrauterine hormonal environmental exposure to oestrogens or anti-androgens, are receiving growing consideration as a risk factor for endometriosis in adult life (23)(24)(25)(26)(27)(28)(29). In addition, accumulating evidence suggests that immune cells, adhesion molecules, extracellular matrix metalloproteinase and pro-inflammatory cytokines activate/alter peritoneal microenvironment, creating the conditions for differentiation, adhesion, proliferation, and survival of ectopic endometrial cells (30,31).…”
Section: Agd and Endometriosismentioning
confidence: 99%
“…The exact etiology of endometriosis is unknown [3]. Several factors such as the genetic and immunological profile, the local inflammation, the hormonal activity and the metabolism of prostaglandins have been suggested to be involved in the onset and/or development of endometriosis [4]. From an epidemiological point of view, numerous hypotheses have been proposed and various investigations conducted to clarify the etiology of this disorder [5,6].…”
Section: Introductionmentioning
confidence: 99%